Effect of Transmission Line Configuration on the Installation of Surge Arrester - Ninh, Van Nam; Pham, Hong Thinh; Tran, Van Top (Old Journal, 2018)
As a transmission line has a specific configuration at an operating voltage, the installation of surge arresters thereof has to take into account the line configuration in order to achieve the best total flash rate. This paper deals with the characteristics in installing surge arresters in the 110 kV and 220 kV transmission lines in Vietnam. Best locations of surge arresters in a given line are determined by studying the effect of main parameters of the transmission lines, such as the type of tower, the number of shield wire, the number of surge arrester to be installed and the footing resistance. The total flashover rate of each transmission line was calculated by the electrogeometric model (EGM) and the electromagnetic transient program simulation (EMTP/ATP), which can be used as a practical guide for the utilities.